PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE ROTATING TRIO EXCHANGE (RTE) DISERTAI MEDIA QUESTION BOX UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI IPA SMA NEGERI 14 PEKANBARU - Desfi Annisa Annisa; Elva Yasmi Yasmi; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research has been conducted on chemical equilibrium subject in XI IPA 3 class SMAN 14 Pekanbaru. Purpose from this research is to find out the achievement of completness learning students on chemical equilibrium subject in XI IPA 3 class SMAN 14 Pekanbaru. Form of this research is pre-experimental research with One-ShotStudy Casedesign. Time for data collection is start from November until December 2014. The selected sample is one from three classes, which is XI IPA 3class. This Class has been selected because in the learning process it seen students with lower activity and lacking motivation. Data analysis technique used in this research is with calculate the percentage of completeness of classical study. Based on result final data processing research obtained classical learning completeness at 90%, its means the implementation of active learning strategy Rotating Trio Exchange (RTE) typewith Question Box media can achieve completeness learning students on chemical equilibrium subject in XI IPA class SMAN 14 Pekanbaru.Keywords: Rotating Trio Exchange (RTE), Question Box media,Mastery Learning, chemical bonds.